Triangular Theory of Love in The Poem "Elegi Hemostasis" by Wira Nagara: A Stylistic Study - Fajar, Yufi Safwan; Nurhayati, Enung (JLER (Journal of Language Education Research), 2025)
ABSTRACT Literary work is a manifestation of concepts and reflections conveyed by a writer. Poetry as a literary genre often explores various aspects of life, including emotions, education, economics, society, politics, and culture. The aim of this research is to identify the triangular theory of love, which consists of three elements: intimacy, passion, and commitment. Understanding the deeper meaning of the poem "Elegy of Hemostasis" written by Wiranagara. This study employs a stylistic methodology based on the theoretical framework proposed by Geoffrey Leech and Michael Short (1981). The study utilizes descriptive and interpretative stylistic methodology. The poem "Elegy of Hemostasis" by Wiranagara serves as the primary data source for this research. The result of this research is that through a stylistic study of the triangular theory of love, it can be seen that this poem not only speaks about the experience of passionate love but also the process of searching for meaning, letting go of the past, and the commitment to create a new love. Each element of love in Sternberg's theory appears in the form of symbols, diction, and imagery that provide deep meaning to the emotional journey experienced by the speaker in the lyrics.Every love poem written by Wiranagara conveys a different interpretation of love and always ends either with sadness or happiness.